A Forward-Looking Commentary: China's Agricultural Development - Priya A. Roy (Journal of Global Initiatives, 2010)
This paper describes China's agricultural development before the reform period from institutional, economic, and ideological perspectives; the reform period; the 11th 5-year plan; and the current situation. The paper gives two case examples of the Soviet Union and India. Finally, the paper ends with a discussion of what this means for China.